2003
DOI: 10.1002/nme.883
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of the Helmholtz equation with high wavenumbers

Abstract: SUMMARYThis paper investigates the pollution effect, and explores the feasibility of a local spectral method, the discrete singular convolution (DSC) algorithm for solving the Helmholtz equation with high wavenumbers. Fourier analysis is employed to study the dispersive error of the DSC algorithm. Our analysis of dispersive errors indicates that the DSC algorithm yields a dispersion vanishing scheme. The dispersion analysis is further confirmed by the numerical results. For one-and higher-dimensional Helmholtz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 34 publications
3
62
0
1
Order By: Relevance
“…It should be emphasized that for M = m = 16, the parameter r could be even larger than 2.8, if a smaller l is used. In fact, the range 2.3 ≤ r ≤ 2.8 is sufficiently large for the purpose of selecting optimal r values of the DSC algorithm with M = 16 for scientific computing [24,53]. Similar findings also hold for different M values.…”
Section: End Domentioning
confidence: 60%
See 3 more Smart Citations
“…It should be emphasized that for M = m = 16, the parameter r could be even larger than 2.8, if a smaller l is used. In fact, the range 2.3 ≤ r ≤ 2.8 is sufficiently large for the purpose of selecting optimal r values of the DSC algorithm with M = 16 for scientific computing [24,53]. Similar findings also hold for different M values.…”
Section: End Domentioning
confidence: 60%
“…In the DSC spatial approximation of the LSTD method, apart from the different half computational bandwidth M can be freely chosen, there is a parameter r in the DSC algorithm which can be adjusted to deliver higher accuracy for the same M [22]. In practice, one can select the desired DSC parameters M and r according to the nature of the problem under consideration by means of the discrete Fourier analysis [24,53]. In the present study, it is found that by using a quite small r, the stability constraint of the LSTD method could be the same after the IDM is carried out.…”
Section: Stability Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Aforementioned methods have found much success in scientific and engineering applications [6][7][8]15,18,20,[25][26][27][28]30,32,34,39,41,40,42,53,54,[57][58][59]. A possible further direction in the field could be the development of higher order interface methods [20,60,61] which are particularly desirable for problems involving both material interfaces and high frequency oscillations, such as the interaction of turbulence and shock, and high frequency wave propagation in inhomogeneous media [5].…”
Section: Introductionmentioning
confidence: 99%